Analisis Perhitungan Beban Pendinginan Ruang Dhammasala Vihara Padumuttara menggunakan Metode CLTD - Ananda Karuna Jaya; Caesar Ondolan Harahap; Rahmi Andarini (Ultima Computing : Jurnal Sistem Komputer, 2020)
Dhammasala room of Padumuttara Temple has an indoor temperature of 28,56oC and relative humidity of 80,6%. According to SNI 03-6572-2001 and a previous literature study, this temperature is outside the thermal comfort zone for tropical climate. Aiming to improve thermal comfort of Dhammasala room with an HVAC system efficiently, the cooling load of the room is analyzed using the Cooling Load Temperature Difference (CLTD) method. The results are also compared with results from other cooling load calculation sofware. The recommended HVAC System for Dhammasala room of Padumuttara Temple is a chiller with a capacity of 30-40TR.